Conversation of pesticide residues into ammonium nitrogen (NH4 +-N) through AOPs and its fertilization effect on lettuce growth - Dong He; Yujiao Wen; Shangzhi Wei; Shikai Li; Lide Liu; Jinmeng Wu; Zhi Zhou; Nan Zhou; Hongmei Liu; Zhonghua Zhou (Biochar, 2025)
Abstract Eliminating pesticide residues in soil through the Advanced Oxidation Processes (AOPs) has been attracted a lot of attention in recent years. However, the potential of converting them into small molecular nutrients such as ammonium nitrogen (NH4 +-N) has been significantly ignored. Herein, we systematically detected the transformation of clothianidin (CTD) into NH4 +-N through AOPs and the following effect on the growth of lettuce. Fe3S4-loaded biochar (BC@Fe3S4) was synthesized in one step through hydrothermal method, possessing excellent catalytic capacity to activate peroxymonosulfate (PMS). The results showed that the generated NH4 +-N could reach up to 3.029 mg L−1 in soil–water system containing 20 mg L−1 of CTD after the treatment of BC@Fe3S4 + PMS. However, when the concentration of CTD in soil was 20 mg kg−1, the dry weight of lettuce was 17.3 mg/plant, and the dry weight of lettuce in CTD-contaminated soil with this concentration was 29.3 mg/plant after treatment by BC@Fe3S4 + PMS, and no CTD residue was detected. The results of lettuce cultivation showed that CTD in the system was converted to NH4 +-N after treatment with BC@Fe3S4 + PMS, which resulted in increased dry matter accumulation and decreased residue of lettuce seedlings. Meanwhile, LC–MS/MS analysis revealed three main degradation routes involved in the CTD degradation process. T.E.S.T-QSAR was carried out to simulate the toxicity of all degradation intermediates to Fathead minnow and T.pyriformis, manifesting that the CTD toxicity decreased after BC@Fe3S4 + PMS treatment. Further analysis indicated that the degradation of CTD and the formation of NH4 +-N occurred simultaneously, where •OH, 1O2 and SO4 •− played a leading role in trigging those reactions. This work explains in detail the mechanism by which pesticides are converted into nutrients, providing feasible strategies and new perspectives for soil remediation. Graphical Abstract